2002
DOI: 10.1159/000059372
|View full text |Cite
|
Sign up to set email alerts
|

Multifetal Gestation – Maternal and Perinatal Outcome of 112 Pregnancies

Abstract: Purpose: Multifetal pregnancy reduction is a widespread ‘therapy’ to diminish the risk of prematurity and adverse outcome for the survivors in higher order multiple gestation. The aim of our study was to determine the maternal and neonatal outcome of multifetal pregnancies under a conservative pregnancy management. Study Design: A retrospective review of 112 multifetal pregnancies is presented. All higher order multiple pregnancies delivered after 25 weeks of gestation and managed at a single institution betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
1
10

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 15 publications
(18 reference statements)
4
44
1
10
Order By: Relevance
“…6,19 However, a number of small series comprising two to 10 sets have reported perinatal losses ranging from as low as 0 to as high as 25%. 7,20 More recently, Strauss et al 8 reported survival rate of 94.5% in a series of 14 quadruplets. However, it is difficult to extrapolate our results with other populations in that data set and this study has been collected from three hospitals over a 15-year period, during which neonatal care may have changed.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…6,19 However, a number of small series comprising two to 10 sets have reported perinatal losses ranging from as low as 0 to as high as 25%. 7,20 More recently, Strauss et al 8 reported survival rate of 94.5% in a series of 14 quadruplets. However, it is difficult to extrapolate our results with other populations in that data set and this study has been collected from three hospitals over a 15-year period, during which neonatal care may have changed.…”
Section: Discussionmentioning
confidence: 98%
“…Unfortunately, studies evaluating the perinatal outcome of higher order multiples have rarely addressed the type of placentation. [6][7][8] Anecdotal case reports have described quadruplet pregnancies with an MC pair after embryo transfer. 9,10 But no study has systematically evaluated the perinatal outcome in higher order pregnancies in relation to chorionicity.…”
Section: Introductionmentioning
confidence: 99%
“…El embarazo múltiple se asocia a un incremento de la patología materna (9). Pocas pacientes con embarazo triple cursan sin alguna complicación.…”
Section: Discussionunclassified
“…La anemia materna según la serie de Seoud y cols (35) se presenta con una frecuencia de 23,1%, mientras que Strauss y cols informan una frecuencia de 5,3% (9). En nuestra serie se presentó anemia moderada en 7 de los 11 casos.…”
Section: Discussionunclassified
See 1 more Smart Citation